ANALYSIS OF EDUCATION QUALITY USING THE PSYCHOLOGICAL CROSS-CUTTING METHOD AT SD INPRES 12/79 MACANANG, BONE DISTRICT - Abustang, Perawati Bt; Marini, Arita; MS, Zulela (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
AbstractThis research aims to provide an overview of the quality of education in public elementary schools in South Sulawesi. The analysis of education quality is based on four components, graduate quality, learning process, teacher quality, and school management. The data collection techniques used are data mining, including document analysis, interviews, observations, and questionnaires. Research respondents consisted of School Committee members, Parent Representatives, Principals, Vice Principals, Teachers, and Students. The data were analyzed using quantitative and qualitative, then analyzed using the Cross-Cutting method to provide recommendations to the local government and schools. The results show that: (1) the overall quality of education in public elementary schools is categorized as very good in all components, (2) there is a need for improvement in some sub-components, including student competence, learning quality, learning climate, professional development of teachers, school leadership, curriculum, and student management. The cross-cutting score obtained was 96 in the category of A-accreditation.Keywords: Quality of Education; School Management